Anatomical localization of progenitor cells in human breast tissue reveals enrichment of uncommitted cells within immature lobules. - Arendt, Lisa M.; Keller, Patricia J.; Skibinski, Adam.; Goncalves, Kevin.; Naber, Stephen P.; Buchsbaum, Rachel J.; Gilmore, Hannah.; Come, Steven E.; Kuperwasser, Charlotte. (2017)
Introduction: Lineage tracing studies in mice have revealed the localization and existence of lineage-restricted mammary epithelial progenitor cells that functionally contribute to expansive growth during puberty and differentiation during pregnancy. However, extensive anatomical differences between mouse and human mammary tissues preclude the direct translation of rodent findings to the human breast. Therefore, here we characterize the mammary progenitor cell hierarchy and identify the anatomic location of progenitor cells within human breast tissues.; Keywords: analysis of variance, basal progenitor cells, bovine serum albumin, cytokeratin, 3,3-diaminobenzidine, 4′,6-diamidino-2-phenylindole, Dulbecco's modified Eagle's medium, dimethyl sulfoxide, epidermal growth factor, estrogen receptor alpha, fluorescence-activated cell sorting, luminal progenitor cells, mature basal, myoepithelial, mammary epithelial cells, mature luminal, mammary lineage negative, phosphate-buffered saline, progesterone receptor, smooth muscle actin, spanning-tree progression analysis of density-normalized events, terminal ductal lobular units.; Springer Open.